Development of a filter for phycocyanin bio-optical estimation - Ogashawara, Igor; Curtarelli, Marcelo P.; Mishra, Deepak R.; Alcântara, Enner H. [UNESP]; Stech, Jose L. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Phycocyanin is a unique pigment for cyanobacteria in inland waters which has been identified by remote sensing. Several band ratio algorithms were developed to estimate and identify phycocyanin using its absorption spectral characteristics. However, other water column constituents influence the remote sensing reflectance measurements at the PC absorption wavelengths. To remove these interferences from the remote sensing reflectance spectra, we proposed a filter to calculate a new remote sensing reflectance for the target wavelengths. The filter showed a better performance for phytoplankton dominated environments enhancing its applicability for the quantification of phycocyanin during algal bloom conditions. This filter demonstrates to be useful because of the new Earth Observing Sensors which will include the phycocyanin absorption spectral bands such as the Ocean and Land Color Instrument (OLCI) from the European Space Agency and SABIA-MAR which is a project from two space programs from Brazil and Argentina.
Keywords: Earth Observing System; Environmental monitoring; Geophysical signal processing; Lakes; Water pollution